Peran Pemerintah Desa dalam Pengembangan Desa Wisata - Robyan Bafadal; Maharani Damaradewi (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
One of Indonesia’s key strategies for generating foreign exchange is the development of Tourism Villages. A Tourism Village refers to a rural area that is utilized as a recreational destination due to its natural beauty, cultural uniqueness, and local attractions that appeal to tourists. The development of Tourism Villages inevitably involves the Village Government as the main authority in village administration. Tourism Village development is an integral part of community empowerment, as it encourages local residents to actively participate in village development activities. Through effective empowerment programs, the Village Government can enhance community capacity, increase economic opportunities, and strengthen local potential in a sustainable manner. This study employs a qualitative research approach. The qualitative research process involves several important stages, including formulating research questions, applying appropriate research procedures, collecting specific data from participants, analyzing data inductively from particular themes to broader patterns, and interpreting the meaning of the findings. Using this approach, the study reveals that the role of the Village Government is crucial in planning, managing, and supporting Tourism Village development. Strong leadership, community involvement, and strategic empowerment initiatives are essential factors in ensuring the successful and sustainable development of Tourism Villages in Indonesia.